2016
DOI: 10.1136/bmjopen-2016-011094
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rate and pulse oximetry derived information as predictors of hospital admission in young children in Bangladesh: a prospective observational study

Abstract: ObjectiveHypoxaemia is a strong predictor of mortality in children. Early detection of deteriorating condition is vital to timely intervention. We hypothesise that measures of pulse oximetry dynamics may identify children requiring hospitalisation. Our aim was to develop a predictive tool using only objective data derived from pulse oximetry and observed respiratory rate to identify children at increased risk of hospital admission.SettingTertiary-level hospital emergency department in Bangladesh.ParticipantsCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…This simple model is derived from predictors that are readily available globally at relatively low cost and can be easily measured by low skilled frontline health workers. The predictors included in the model reflect what has been observed in previous studies [28][29][30] and what is often included in international guidelines 31 . After internal validation, the model affords high discrimination, with an AUC of 0.88 (95% CI 0.82 to 0.94) and good calibration (p = 0.715).…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple model is derived from predictors that are readily available globally at relatively low cost and can be easily measured by low skilled frontline health workers. The predictors included in the model reflect what has been observed in previous studies [28][29][30] and what is often included in international guidelines 31 . After internal validation, the model affords high discrimination, with an AUC of 0.88 (95% CI 0.82 to 0.94) and good calibration (p = 0.715).…”
Section: Key Resultsmentioning
confidence: 99%
“…The digital platform also allows for real time monitoring of user performance and compliance and optimization of work flows. In addition, pulse oximetry can be conducted with mobile device by attaching low-cost sensors to enable objective measurements and alleviate the need to perform manual data entry of values read from a separate monitor 30,33,34 . The inclusion of RRate, an app for measure respiratory rate by tapping on the screen also enables faster collection of respiratory rate with less effort than counting breaths 12 .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Thus, PaO 2 variability could be a surrogate marker for relative ischemiareperfusion injury in the brain, which could cause secondary brain injury. Indeed, in pediatric intensive care, oxygen variability measured on the plethysmography has recently been shown to predict chronic lung disease [11,12] or the need for hospitalization [12].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, PaO 2 levels > 100 mmHg seem to have deleterious effects on outcome in critically ill patients overall [6,7] and the threshold changes only slightly in specific subpopulations such as post-cardiac arrest (PaO 2 levels > 120 mmHg) [8,9] or aneurysmal subarachnoid hemorrhage (aSAH) (PaO 2 > 200 mmHg) patients [10]. Moreover, the concept of PaO 2 variability, defined as the daily difference between the highest and the lowest PaO 2 values, has recently been identified as a potential surrogate marker for relative ischemiareperfusion injury [11,12].…”
mentioning
confidence: 99%
“…For pneumonia, (one of the most common causes of hypoxemia especially in children), hypoxemia is primarily caused by obstruction of oxygen exchange in the alveoli of the lungs. A systematic review found that hypoxemia is a strong predictor of mortality for pneumonia in children, and other studies have also found hypoxemia to be associated with mortality and other poor outcomes for other diseases [1][2][3][4][5][6]. Patients in low-and middle-income countries (LMICs) are disproportionately affected as oxygen therapy, an effective treatment of hypoxemia, is not widely accessible [7,8].…”
Section: Introductionmentioning
confidence: 99%